Pooled microbiological findings and efficacy outcomes by pathogen in adults with community-acquired bacterial pneumonia from the Lefamulin Evaluation Against Pneumonia (LEAP) 1 and LEAP 2 phase 3 trials of lefamulin versus moxifloxacin. (June 2022) - Paukner, Susanne; Goldberg, Lisa; Alexander, Elizabeth; Das, Anita F.; Heinrich, Stefanie; Patel, Pritty; Moran, Gregory J.; Sandrock, Christian; File, Thomas M.; Vidal, Jorge E.; Waites, Ken B.; Gelone, Steven P.; et al.
Highlights: Lefamulin showed potent activity against the most common community-acquired bacterial pneumonia (CABP) pathogens. Bacterial baseline pathogens were identified by real-time quantitative PCR and standard diagnostic tests. Lefamulin efficacy was high regardless of baseline pathogen or presence of drug-resistant strains/polymicrobial infection. ABSTRACT: Objectives: Lefamulin, a pleuromutilin antibiotic approved for community-acquired bacterial pneumonia (CABP), was evaluated for microbiological efficacy in a prespecified pooled analysis of LEAP 1 and 2 phase 3 clinical trial data in patients with CABP. Methods: In LEAP 1, adults (PORT risk class III‒V) received intravenous (IV) lefamulin 150 mg every 12 h (q12h) for 5‒7 days or moxifloxacin 400 mg every 24 h (q24h) for 7 days, with optional IV-to-oral switch. In LEAP 2, adults (PORT II‒IV) received oral lefamulin 600 mg q12h for 5 days or moxifloxacin 400 mg q24h for 7 days. Primary outcomes were early clinical response (ECR) at 96 ± 24 h after treatment start and investigator assessment of clinical response (IACR) 5‒10 days after the last dose. Secondary outcomes included ECR and IACR in patients with a baseline CABP pathogen (detected via culture, urinary antigen testing, serology and/or real-time PCR). Results: Baseline CABP pathogens were detected in 709/1289 patients (55.0%; microbiological intention-to-treat population). The most frequently identified pathogens were Streptococcus pneumoniae (61.9% of patients) and Haemophilus influenzae (29.9%); 25.1% had atypical pathogens and 33.1% had polymicrobial infections. Pathogens were identified most frequently by PCR from sputum, followed by culture from respiratory specimens. In patients with baseline CABP pathogens, ECR rates were 89.3% (lefamulin) and 93.0% (moxifloxacin); IACR success rates were 83.2% and 86.7%, respectively. Results were consistent across CABP pathogens, including drug-resistant isolates and polymicrobial infections. Conclusion: Lefamulin is a valuable IV and oral monotherapy option for empirical and directed CABP treatment in adults.